Seasonal plasma electrolyte fluctuations in childhood diarrhoea. Issue 5 (1st November 2002) - Swingler, G; Power, D
Abstract : A retrospective analysis of routinely collected data from a diarrhoea rehydration unit found clinically meaningful parallel seasonal variation in plasma sodium and potassium concentrations. The prevalence of severe hypokalaemia was 7.2% and 0.4% in February and August respectively, and of severe hypernatraemia 0.4% and 5.0% respectively. These unexpected findings need prospective confirmation and exploration in other settings.